Biosynthesis and purification of DNA vectors as therapeutic approaches against Human Papillomavirus infection - Almeida, Ana Margarida Cardoso Valério de (2021)
Cervical cancer is one of the leading causes of death amongst women, especially in countries lacking suitable access to health and hygiene care. Contrarily to most cancers, which usually take origin in mutations related with the action of mutagenic or carcinogenic agents, the development of cervical cancer is strongly associated with infection by Human Papillomavirus (HPV). This virus is responsible for the expression of E6 and E7 oncoproteins, which interfere with the cell cycle regulation, affecting the cellular mechanisms of repair and proliferation of infected cells. In the last decades, DNA-based therapies, such as DNA vaccines or gene therapy, have been highly explored by researchers in the search of an efficient non-viral vector for the cervical cancer treatment. Plasmid DNA (pDNA) is a popular non-viral vector, which has been widely studied in the past decades for the development of a variety of DNA vaccines and gene therapy strategies. However, the presence of CpG motifs necessary to its amplification in prokaryotic hosts may lead to the activation of the immune system and to the degradation of this molecule before it can reach the target cells, in a gene therapy perspective. However, these same motifs may contribute to the recognition of this bioproduct by antigen presenting cells, facilitating the processing of pDNA as a DNA vaccine. Minicircle DNA (mcDNA) consists in a non-viral vector whose popularity has been largely increasing in the last years. This vector results from the recombination of a molecule, which is similar to conventional pDNA, named parental plasmid (PP). However, PP presents two recombination sites which, upon induction, give origin to the recombination of this molecule into two different molecules: one containing all the prokaryotic information necessary for PP amplification in prokaryotic hosts (miniplasmid – mP) and another containing all the information necessary for the therapeutic gene expression in eukaryotic cells (mcDNA). Considering its innovative character, it is crucial to develop suitable strategies for mcDNA preparation, with a purity that fits the requirements established by regulatory agencies such as European Medicines Agency (EMA) or Food and Drug Administration (FDA). Thus, this work was performed with two different perspectives regarding cervical cancer treatment, namely DNA vaccines and gene therapy. Firstly, concerning DNA vaccines, the application of an adequate purification strategy allowed to understand that the purity degree of the pDNA sample can significantly contribute for the increased expression of the target antigen. The application of a monolith modified with arginine ligands, comparatively to the use of commercially available techniques, allowed to retrieve a final DNA vaccine sample with higher supercoiled (sc) content, leading to a higher expression of the target proteins. Concomitantly, the development of nanocarriers composed by calcium carbonate and gelatin allowed the delivery of pDNA vaccine to dendritic cells, also known as antigen presenting cells, without detecting cytotoxicity. On the other hand, two different strategies for mcDNA purification were explored. Firstly, the preparation of a monolith modified with cadaverine ligands and its use in the purification of sc mcDNA allowed a recovery yield of 78.6% coupled with 98.4% purity. These results turned out to be very interesting considering the current mcDNA purification scenario in the literature. On the other side, size exclusion chromatography was also explored through the use of Sephacryl SF-1000 matrix. This strategy allowed to obtain a sc mcDNA yield of 66% alongside a purity of 98.35%. Despite 12 times more mass of pure sc mcDNA was obtained in one assay, the assay turned out to be approximately 8 times longer than the assays performed with the cadaverine modified monolith. In the end, two strategies were developed for sc mcDNA purification, each presenting its advantages and disadvantages. Nonetheless, both allowed the purification of mcDNA without resorting to PP specific genetic modifications, which implies that these strategies can be universally used for mcDNA purification. However, the need to implement an analytical methodology that allows to quantify sc mcDNA content in a fast, low cost and effective way led to the study of cadaverine-modified monolith with this purpose. Thus, a chromatographic method was implemented and validated to quantify sc mcDNA concentration present in a complex or pure sample, within a range of 1-25 μg/mL. Lastly, to study the effectiveness of miR-375 in the treatment of cervical cancer, in vitro studies were performed to evaluate the effect displayed by mcDNA-pri-miR-375 in the expression of E6 an E7 oncoproteins. Therefore, CaSki cell line model was used, which consists in metastatic cervical cancer cells infected by HPV-16. Also, a fibroblast cell line was used as a non-carcinogenic model for control. It was possible to identify the correct expression of miR-375, coupled with a decrease in E6 and E7 transcript and protein levels. Furthermore, it was observed that fibroblast viability was not affected, instead observing a decrease in transfected CaSki proliferation and viability. Thus, the application of mcDNA-pri-miR-375 as a possible therapeutic strategy should be more amply studied in the future. In the end, this thesis presents a scientific work that intends to contribute towards the scientific community with useful information for the potential development of new approaches for cervical cancer treatment, through the implementation of two biotechnological platforms. One of the strategies is based on the obtainment of a DNA vaccine, encoding E6 and E7 HPV antigens with the aim of activating two pathways of the immune system, the preventive/humoral and the therapeutic/cellular pathways, allowing the consequent elimination of the antigen-expressing and HPV-infected cervical cancer cells. The second strategy is focused on the obtainment of innovative gene therapy mcDNA vector, encoding pri-miR-375, to silence E6 and E7 HPV oncoproteins, allowing the direct targeting of infected cervical cancer cells, through the re-establishment of tumor suppressor proteins expression or function.